CHILD FRIENDLY SCHOOL INITIATIVE AT THREE PRIMARY HEALTH CENTERS OF BELGAUM DISTRICT, KARNATAKA - DR. (MRS.) SULAKSHANA S. BALIGA (International Journal of Pharma and Bio Sciences, 2013)
Children between the ages of five-seventeen years are school children. Children spend most of their time during the day in the school. Hence the present study was undertaken to determine how many schools met these 10 commandments for the child friendly school initiative. The aim of the present study is to find out how many schools met the10 criteria of Child Friendly School Initiative. This cross-sectional study was conducted at 3 Primary Health Centre’s, in Belgaum. 60 government primary schools were selected and necessary data related to 10 criteria’s of child friendly school initiatives was collected. In 42% schools, weight of the school bag exceeded 10% of the child’s weight. 82% of schools provided hygienic drinking water. More than 60% of the schools did not have adequate urinals and latrines. We found that none of the schools met all the 10 commandments .Although 50% of them followed 4 to 5 criteria.